Phineas L. MacGuire...gets cooking! - Dowell, Frances O'Roark (Dowell, Frances O'Roark. From the highly scientific notebooks of Phineas L. MacGuire, 2014)
"Phineas has a new chore of cooking dinner every night, but his kitchen experiments take a turn for the worse when the school bully takes a huge liking to Phineas's brownies"--